Phenotypic Changes Exhibited by E. coli Cultured in Space - Zea, Luis; Larsen, Michael; Estante, Frederico; Qvortrup, Klaus; Moeller, Ralf; Dias de Oliveira, Sílvia; Stodieck, Louis; Klaus, David (Frontiers in Microbiology, 2017)
Bacteria will accompany humans in our exploration of space, making it of importance to study their adaptation to the microgravity environment. To investigate potential phenotypic changes for bacteria grown in space, Escherichia coli was cultured onboard the International Space Station with matched controls on Earth. Samples were challenged with different concentrations of gentamicin sulfate to study the role of drug concentration on the dependent variables in the space environment. Analyses included assessments of final cell count, cell size, cell envelope thickness, cell ultrastructure, and culture morphology. A 13-fold increase in final cell count was observed in space with respect to the ground controls and the space flight cells were able to grow in the presence of normally inhibitory levels of gentamicin sulfate. Contrast light microscopy and focused ion beam/scanning electron microscopy showed that, on average, cells in space were 37% of the volume of their matched controls, which may alter the rate of molecule–cell interactions in a diffusion-limited mass transport regime as is expected to occur in microgravity. TEM imagery showed an increase in cell envelope thickness of between 25 and 43% in space with respect to the Earth control group. Outer membrane vesicles were observed on the spaceflight samples, but not on the Earth cultures. While E. coli suspension cultures on Earth were homogenously distributed throughout the liquid medium, in space they tended to form a cluster, leaving the surrounding medium visibly clear of cells. This cell aggregation behavior may be associated with enhanced biofilm formation observed in other spaceflight experiments.